2011
DOI: 10.1371/journal.pone.0025629
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Level Changes the Interactions between a Native (Scirpus triqueter) and an Exotic Species (Spartina anglica) in Coastal China

Abstract: The exotic species Spartina anglica, introduced from Europe in 1963, has been experiencing a decline in the past decade in coastal China, but the reasons for the decline are still not clear. It is hypothesized that competition with the native species Scirpus triqueter may have played an important role in the decline due to niche overlap in the field. We measured biomass, leaf number and area, asexual reproduction and relative neighborhood effect (RNE) of the two species in both monoculture and mixture under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…There are similar processes induced by Spartina townsendii and Spartina angelica in other Pacific coastal marshes, such as in eastern China (Li et al 2011). For example, in coastal salt marshes in Dafeng, Qidong and Jiuduansha, China, the vegetation pattern was mudflat-sedge or mudflat-P. australis before Spartina plants colonized; at present, the vegetation pattern is mudflat-Spartina spp., mudflat-sedge-Spartina spp.…”
Section: Influences Of New Arrival Tolerance To Non-resource Stress Omentioning
confidence: 83%
See 1 more Smart Citation
“…There are similar processes induced by Spartina townsendii and Spartina angelica in other Pacific coastal marshes, such as in eastern China (Li et al 2011). For example, in coastal salt marshes in Dafeng, Qidong and Jiuduansha, China, the vegetation pattern was mudflat-sedge or mudflat-P. australis before Spartina plants colonized; at present, the vegetation pattern is mudflat-Spartina spp., mudflat-sedge-Spartina spp.…”
Section: Influences Of New Arrival Tolerance To Non-resource Stress Omentioning
confidence: 83%
“…More broadly, plants often suffer from harsh environmental conditions within their current and potential distribution ranges. However, while many studies have focused on the tolerance to low resource availability and competition under different levels of resource availability (Grime 1977, Tilman 1985, Tilman 1990, Grace 1991, Li et al 2011, Zhou et al 2012, the effects of the tolerance of new arrivals to non-resource factors on their performance and competitiveness have been relatively ignored.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most consistent findings of tests of this hypothesis has been that an increase in the availability of N can promote the spread of introduced species of plants in terrestrial habitats (Pfeifer-Meister et al 2008;Rao and Allen 2010;Dukes et al 2011;Li et al 2011;Mozdzer and Zieman 2010;Mozdzer and Megonigal 2012). This is of particular ecological interest because anthropogenic increases in N availability through aerial deposition and agricultural application of fertilizers are a major component of global change (Bobbink et al 2010;Henrys et al 2011;McClean et al 2011). Together, this previous work suggests that it would be useful and timely to test whether greater ability to increase performance in response to increase in N availability is associated with greater invasiveness in clonal plant species.…”
Section: Introductionmentioning
confidence: 98%
“…Nutrient enrichment as a result of anthropogenic landscape modifications has also become widely recognized as a serious threat to biodiversity maintenance and ecosystem functioning910. Although many studies have investigated responses of invasive plants and native plant communities to nutrient enrichment1112, impacts of nutrient enrichment on the interaction between invasive plants and native plant communities remains an unresolved issue in invasion biology131415.…”
mentioning
confidence: 99%
“…Many studies have shown that the invasion success of exotic plants can be enhanced by enrichment of nutrients that are limiting27. For example, nitrogen addition enhanced richness and abundance of invasive annual herbs1011, promoted the spread of introduced plants into terrestrial habitats12, but increased the resistance of resident communities to the invasion by Bromus tectorum 28. Thus, different habitat-dependent pathways mediate interactions between invasion and nutrient enrichment to drive community change29.…”
mentioning
confidence: 99%